High Dose IFN-β Activates GAF to Enhance Expression of ISGF3 Target Genes in MLE12 Epithelial Cells - Kishimoto, Kensei; Wilder, Catera L.; Buchanan, Justin; Nguyen, Minh; Okeke, Chidera; Hoffmann, Alexander; Cheng, Quen J. (Frontiers in Immunology, 2021)
Interferon 𝛽 (IFN-𝛽) signaling activates the transcription factor complex ISGF3 to induce gene expression programs critical for antiviral defense and host immune responses. It has also been observed that IFN-𝛽 activates a second transcription factor complex, γ-activated factor (GAF), but the significance of this coordinated activation is unclear. We report that in murine lung epithelial cells (MLE12) high doses of IFN-𝛽 indeed activate both ISGF3 and GAF, which bind to distinct genomic locations defined by their respective DNA sequence motifs. In contrast, low doses of IFN-𝛽 preferentially activate ISGF3 but not GAF. Surprisingly, in MLE12 cells GAF binding does not induce nearby gene expression even when strongly bound to the promoter. Yet expression of interferon stimulated genes is enhanced when GAF and ISGF3 are both active compared to ISGF3 alone. We propose that GAF may function as a dose-sensitive amplifier of ISG expression to enhance antiviral immunity and establish pro-inflammatory states.